Assessing changes in facial skin quality using noninvasive in vivo clinical skin imaging techniques after use of a topical retinoid product in subjects with moderate‐to‐severe photodamage - Goberdhan, Lisa T.; Pellacani, Giovanni; Ardigo, Marco; Schneider, Katie; Makino, Elizabeth T.; Mehta, Rahul C. (Skin research and technology, 2022)
Background Studies utilizing reflectance confocal microscopy (RCM) and dynamic optical coherence tomography (D‐OCT) to assess cosmetic skin changes are limited. Methods A 12‐week, open‐label study was conducted using RCM and D‐OCT to evaluate the effects of a topical cosmetic retinol (RET05) on subjects with facial photodamage. Study endpoints included investigator grading, standardized (VISIA‐CR) and 3D photography (Antera 3D), independent RCM (VivaScope1500) and D‐OCT (VivoSight) image analysis, validated FACE‐Q scales, and subject questionnaires. Results Twenty‐three subjects, 45‐ to 68‐year old, with Fitzpatrick skin types II–IV completed the study. After 12 weeks of repeated application, RET05 demonstrated significant corresponding cosmetic improvements for overall photodamage, skin tone unevenness, tactile roughness, fine lines/wrinkles (forehead, periocular, and perioral), and coarse lines/wrinkles (forehead, periocular, and cheeks), and Allergan Skin Roughness Scale. FACE‐Q assessments also demonstrated significant improvements from baseline at week 12. RCM analysis showed decreases in all epidermis, less compact stratum corneum (SC), more non‐compact SC, decreases in coarse/huddled dermal fibers, and increases in fibrillar dermal fibers, as compared to baseline. D‐OCT analysis showed significant decreases in epidermal thickness (ET), reduction of moderate/many collagen fragments and collagen bundles, and significant increases in the stroma attenuation coefficient and collagen density. Moreover, the dermal–epidermal junction was more pronounced, and vascular abundance at 300 and 500 μm depth increased. Independent evaluation of RCM and D‐OCT images showed similar decreases in ET and improvements in dermal fibers. Conclusion This study was the first to utilize RCM and D‐OCT to evaluate the cosmetic effects of a topical retinoid and further substantiate improvements in skin quality.